Vulnerability of RC Shear wall Structures under Near Field Seismic Loading - Khalil, Mostafa (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Αντισεισμικής Τεχνολογίας, 2018)
In this paper the seismic risk of an eight storey reinforced concrete building in Athens is investigated. The structure is exposed to a near field ground motions from Italian Aquila and Norcia earthquakes, due to the similarity in the geotectonic environment between Greece and Italy. The purpose of this investigation is to estimate the damage occurred to the building and the effect of the seismological parameters such as, moment magnitude, forward directivity, acceleration time history density and amplitude. As a first step, a sample of 16 near fault ground motion records from Aquila and Norcia earthquakes in Italy is exposed to the building, to obtain the displacement time history of each record, which will be used to determine the damage limit states achieved according to “T. Rossetto, A. ElNashai” vulnerability relationships. Then suggesting a solution to improve the seismic response of the building, and an appropriate solution is found and applied according to the new Chilean seismic code provisions which states that typical buildings include a large number of shear walls, with ratios of wall cross-sectional area to floor plan area of roughly 3% in each principal direction, with light reinforcement. After implementing the Chilean code provisions and investigating the building in Y-direction only, the results have shown a significant improvement in the building response and a reduction in the damage limit states reached for most of the records. After reviewing all the results, it was found that the moment magnitude value isn’t the predominant affecting factor, and the acceleration time history density is more effective in the damage caused by the near field records. Eventually, it is concluded that estimation of damage intensity is mostly affected by the energy contained in the ground motion which is introduced as the “energy flux” index.